Teamwork and Leadership Under Fire at the Epicenter of the COVID-19 Epidemic in the Bronx - Tomer, Yaron; Ng Gong, Michelle; Keller, Marla J.; Southern, William; Kitsis, Elizabeth A.; Kajita, Grace R.; Shapiro, Lauren I.; Jariwala, Sunit P.; Epstein, Eric J. (Frontiers in Medicine, 2021)
The first Covid-19 patient was admitted to Montefiore Medical Center (MMC) on March 10, 2020. Soon thereafter there was a rapid and exponential surge of Covid-19 admissions to MMC that could have resulted in catastrophic consequences if MMC had been overwhelmed, as happened in Europe. To adjust to this crisis our institution, under the inspiring leadership of Dr. Philip Ozuah, President and CEO of Montefiore Medicine, adopted an “all hands on deck” approach, mobilizing our entire workforce to expand our units to accommodate the growing number of patients being admitted. Given that the internal medicine (IM) and ICU units are part of the department of medicine (DOM), the DOM was at the center of this mobilization. The DOM is the largest department at MMC and mobilizing it required careful planning, seamless teamwork, and strong leadership. To achieve that goal, we applied a framework that we designate the “3C framework,” denoting Coordination, Communication, and Collaboration. In this report we describe the many initiatives the Montefiore Einstein DOM implemented during the Covid-19 pandemic using the 3C framework. These included establishing the Medicine Covid-19 Taskforce to lead our efforts, starting a daily newsletter for up-to-date communications, rapidly expanding the ICU and IM units, converting most specialty inpatient consults to eConsults, coordinating research studies, and more. The goal of this report is to serve as a guide on how the 3C framework helped us organize, mobilize, and energize the department of medicine effectively and efficiently during this unprecedented crisis.